2006
DOI: 10.1016/j.jinf.2005.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive outcome in adults with moderate disability after pneumococcal meningitis

Abstract: Summary Objectives: To assess cognitive outcome and quality of life in patients with moderate disability after bacterial meningitis as compared to patients with good recovery. Methods: Neuropsychological evaluation was performed in 40 adults after pneumococcal meningitis; 20 patients with moderate disability at discharge on the glasgow outcome scale (GOS score 4) and 20 with good recovery (GOS score 5). Results: Patients with GOS score 4 had similar test results as compared to patients with GOS score 5 for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 17 publications
5
23
1
Order By: Relevance
“…Previous studies on cognitive outcome in adults who survived bacterial meningitis described cognitive slowness, impairment of psychomotor and visuoconstructive performance, and higher scores on depression scales. 5,27,[33][34][35] Our findings agree with previous observations. 5,27,33 Hippocampal damage has been related to learning and memory deficits in humans and in animal models.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Previous studies on cognitive outcome in adults who survived bacterial meningitis described cognitive slowness, impairment of psychomotor and visuoconstructive performance, and higher scores on depression scales. 5,27,[33][34][35] Our findings agree with previous observations. 5,27,33 Hippocampal damage has been related to learning and memory deficits in humans and in animal models.…”
Section: Discussionsupporting
confidence: 93%
“…5,27,[33][34][35] Our findings agree with previous observations. 5,27,33 Hippocampal damage has been related to learning and memory deficits in humans and in animal models. 10 This suggests that neuronal apoptosis in the hippocampal dentate gyrus represents the major neuropathological process responsible for cognitive impairment in survivors of bacterial meningitis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…From a neuropsychological point of view, the hippocampal predominance of volume loss might explain a considerable part of the memory dysfunctions that survivors of BM often experience. 11,15,16 In our previous study in the same cohort, 11 we found significantly worse neuropsychological performance in BM for working memory, executive, and visoconstructive functions.…”
Section: Discussionmentioning
confidence: 49%